Developing programs for preschool children to enhance Chinese literacy: A Macau-based example - Chu, K. W.; Mak, M. C. K; Tse, T. P. M.; Cheng, P. W.; Ho, G. W. S.; Ng, M. H.; Ng, S. K. (2023)

Enhancing Teacher Education by Utilizing a Revised PGDE Curriculum as a Fundamental Resource for Inclusive Practices in Macao - Monteiro, Elisa; Forlin, Chris (International Perspectives on Inclusive Education, 2021)
Keywords: Inclusive education; Knowledge transfer; Pedagogical practice; Post-graduate diploma in education; Programme design; Teachers

Home–School Collaboration in Assessment, Placement, and Individual Education Plan Development for Children With Special Education Needs in Macao: The Views of Parents - Correia, Ana; Teixeira, Vitor; Forlin, Chris (School Community Journal, 2021)
The aim of this study was to explore home–school collaboration in the areas of assessment, placement, and Individual Education Plan (IEP) development for children identified with disabilities or special educational needs (SEN) in Macao. Despite the noted benefits of parent–school partnerships from prior research, minimal research has been conducted from the perspective of parents of children with SEN to examine whether these partnerships materialize in the context of Macao. Participants included 115 parents of school-aged children diagnosed with SEN. They provided demographic information and completed a 36-item questionnaire derived from two validated instruments. The research identified a range of factors which hinder parental involvement in decision-making and in the inclusion of children with SEN in optimal ways in Macao schools. Parents indicated they were not receiving relevant information and assessment feedback from the teachers; they were minimally involved in the IEP process, and their children were not receiving one-to-one support, regardless of the type of placement. Parents also underlined issues related to the timing of assessment procedures. Parents of children attending special classes in regular schools voiced more satisfaction with support provision than parents of children following the full inclusion model. Recommendations about how services could be improved for greater parental involvement are discussed. Key Words: parental involvement, school–family collaboration, inclusion, special educational needs, Macao, Individual Education Plans, IEP

Towards a framework of teacher professional development: The case of early literacy education in Macau - Tse, T. P. M.; Mak, M. C. K; Chu, K. W.; Cheng, P. W.; Ho, G. W. S.; Chan, A. O. K; Ng, M. H.; Leong, K. I. Q. (2022)

Validating the use of the 24-item long version and the 12-item short version of the Teachers’ Sense of Efficacy Scale (TSES) for measuring teachers’ self-efficacy in Macao (SAR) for inclusive education - Monteiro, Elisa; Forlin, Chris (Emerald Open Research, 2020)
Validation of the Teachers’ Sense of Efficacy Scale (TSES) for use with teachers in Macao (SAR) was undertaken to determine its usefulness as a measure of teacher self-efficacy for inclusive education. This paper discusses the results found by analyzing various versions of the TSES and TSES-C in a Chinese format with 200 pre-service teachers in Macao (SAR).  Psychometric analyses were undertaken to investigate the validity of the existing scales and the three and two factor solutions. The results indicated a preferred 9-item version that produced improved factor loadings and reliabilities. The use of a relatively quick and short scale to measure such a complex phenomenon as teacher self-efficacy is discussed. Issues are raised regarding generalizability of scales and the impact of culture, demographics, and edifying issues that may impact on the usefulness of such scales.
Type: article
Keywords: Inclusive education; Macao; scale development; self-efficacy